Coexistence between similar invaders: The case of two cosmopolitan exotic insects - Matthew B. Arnold; Michael Back; Michael Daniel Crowell; Nageen Farooq; Prashant Ghimire; Omon A. Obarein; Kyle E. Smart; Trixie Taucher; Erin VanderJeugdt; Kayla I. Perry; Douglas A. Landis; Christie A. Bahlai (Ecology, 2023)
Biological invasions are usually examined in the context of their impacts on native species. However, few studies have examined the dynamics between invaders when multiple exotic species successfully coexist in a novel environment. Yet, long‐term coexistence of now established exotic species has been observed in North American lady beetle communities. Exotic lady beetles Harmonia axyridis and Coccinella septempunctata were introduced for biological control in agricultural systems and have since become dominant species within these communities. In this study, we investigated coexistence via spatial and temporal niche partitioning among H. axyridis and C. septempunctata using a 31‐year data set from southwestern Michigan, USA. We found evidence of long‐term coexistence through a combination of small‐scale environmental, habitat, and seasonal mechanisms. Across years, H. axyridis and C. septempunctata experienced patterns of cyclical dominance likely related to yearly variation in temperature and precipitation. Within years, populations of C. septempunctata peaked early in the growing season at 550 degree days, while H. axyridis populations grew in the season until 1250 degree days and continued to have high activity after this point. C. septempunctata was generally most abundant in herbaceous crops, whereas H. axyridis did not display strong habitat preferences. These findings suggest that within this region H. axyridis has broader habitat and abiotic environmental preferences, whereas C. septempunctata thrives under more specific ecological conditions. These ecological differences have contributed to the continued coexistence of these two invaders. Understanding the mechanisms that allow for the coexistence of dominant exotic species contributes to native biodiversity conservation management of invaded ecosystems.

Vacant lot soil degradation and mowing frequency shape communities of belowground invertebrates and urban spontaneous vegetation - Kayla I. Perry; Nicole C. Hoekstra; Steve W. Culman; Mary M. Gardiner (Urban Ecosystems, 2021)

Characterizing Movement of Ground-Dwelling Arthropods with a Novel Mark-Capture Method Using Fluorescent Powder - Kayla I. Perry; Kimberly F. Wallin; John W. Wenzel; Daniel A. Herms (Journal of Insect Behavior, 2017)

Mechanisms underlying plant sexual dimorphism in multi‐trophic arthropod communities - William K. Petry; Kayla I. Perry; Aleshia Fremgen; Sarah K. Rudeen; Mitchell Lopez; John Dryburgh; Kailen A. Mooney (Ecology, 2013)
A growing body of research documents the importance of plant genetic effects on arthropod community structure. However, the mechanisms underlying these effects are often unclear. Additionally, plant genetic effects have largely been quantified in common gardens, thus inflating the estimates of their importance by minimizing levels of natural variation. Using Valeriana edulis , a dioecious plant with genetically based sex determination, we conducted surveys and experiments on wild‐grown individuals to document field patterns of arthropod association between the sexes and the mechanisms underlying these plant genetic effects. Three years of surveys revealed strong and consistent sex‐biased arthropod association in wild‐grown plants: female plants supported 4‐fold, 1.5‐fold, and 4‐fold higher densities of aphids, aphid predators, and aphid‐tending ants, respectively, compared to males. There was mixed evidence that the female bias for aphids was due to higher plant quality, while we found no difference between plant sexes in aphid preference or the top‐down effects of predators and tending ants. Female bias for ants was due to both the greater attractiveness of female plants (direct effect mediated by floral nectar) and an independent, weaker effect of higher aphid abundance on females (density‐mediated indirect effect). Conversely, the female bias for predators was driven solely by the greater attractiveness of female plants. We did not find interaction modification, i.e., ant–aphid and predator–aphid interactions were equivalent between plant sexes. Plant sex explained 0.24%, 2.28%, and 4.42% of the variance in aphids, predators, and ants, respectively, values comparable to but slightly weaker than those previously reported from common‐garden studies. In contrast to the prediction of diminished plant genetic effects with increasing trophic level, we show how weak indirect effects on predators and parasitoids (via herbivores) can be complemented by strong direct effects via common plant traits (floral resources). In summary, we document direct and indirect effects of genetically based sex on a multi‐trophic arthropod community that were expressed in wild‐grown plants across multiple years.